2008
DOI: 10.1007/s11926-008-0027-4
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid factors and anticyclic citrullinated peptide antibodies in pediatric rheumatology

Abstract: Juvenile idiopathic arthritis (JIA) is a heterogenous childhood disease without reliable biomarkers for monitoring disease progression. Immunoglobulin (Ig) M rheumatoid factor (RF) is used to define a subset of JIA patients, but its significance in JIA is dependent on the method of measurement. In addition to IgM RF, IgA RF has been implicated in determining disease severity in JIA, including functional disability and joint damage. Anticyclic citrullinated peptide (anti-CCP) antibodies have been a valuable dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 41 publications
(50 reference statements)
5
25
0
1
Order By: Relevance
“…Also other studies done by Syed et al supported our study in the likely effectiveness of anti-CCP antibodies in observing JIA patients to determine the consequences of the disease. In general, RF isotypes and anti-CCP isotypic antibodies have revealed growing importance in the evaluation of JIA patients to ascertain which patients may have more aggressive or severe disease and to support treatment plans likely to prevent joint damage and disability (10). Consistent with this information, the most recent work by Gupta et al revealed anti-CCP antibodies could be identified more regularly in the sera of JIA patients with severe manifestations such as erosions and deformity which was also indicated in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also other studies done by Syed et al supported our study in the likely effectiveness of anti-CCP antibodies in observing JIA patients to determine the consequences of the disease. In general, RF isotypes and anti-CCP isotypic antibodies have revealed growing importance in the evaluation of JIA patients to ascertain which patients may have more aggressive or severe disease and to support treatment plans likely to prevent joint damage and disability (10). Consistent with this information, the most recent work by Gupta et al revealed anti-CCP antibodies could be identified more regularly in the sera of JIA patients with severe manifestations such as erosions and deformity which was also indicated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the possible significance of anti-CCP antibodies in monitoring JIA patients to predict the disease outcome. Generally, RF and anti-CCP antibodies have demonstrated great importance in JIA patients evaluation to predict which patients may have more aggressive or severe disease and to determine possible treatment plans to prevent joint damage and disability (10). Furthermore, anti-CCP antibodies are effective markers of disease activity.…”
Section: Page 2898mentioning
confidence: 99%
“…In the lab, the authors have studied the role of anti-CCP antibodies in both adult RA patients and also in JIA patients. Significance of anti-CCP antibodies in JIA remains undermined, with several studies showing IgM RF-positive polyarticular JIA patients, those who most closely resemble adult RA patients, having a higher prevalence of anti-CCP antibodies [41]. Studies in JIA, including the authors' own research, have demonstrated that the presence of anti-CCP antibodies may play a role in the pathogenesis of JIA, and perhaps more specifically in the development of joint damage [41].…”
Section: Expert Opinionmentioning
confidence: 98%
“…Significance of anti-CCP antibodies in JIA remains undermined, with several studies showing IgM RF-positive polyarticular JIA patients, those who most closely resemble adult RA patients, having a higher prevalence of anti-CCP antibodies [41]. Studies in JIA, including the authors' own research, have demonstrated that the presence of anti-CCP antibodies may play a role in the pathogenesis of JIA, and perhaps more specifically in the development of joint damage [41]. The authors' research has also shown that IgG anti-CCP antibodies demonstrated a high specificity for JIA (94.7%), and also specifically in patients with polyarticular disease resembling adult RA (93.9%) [42].…”
Section: Expert Opinionmentioning
confidence: 99%
“…Recent studies have evaluated the role of anti-CCP in JIA in diagnosis and prediction of disease outcome and found that anti-CCP can be detected mainly in patients with polyarthritic onset and who are RF positive (Avcin et al, 2002;Ferucci et al, 2005;Dewint et al, 2006;Syed et al, 2008). Although these ACPAs have similar sensitivities and specificities in diagnosing RA, because they differ in terms of the antigen source, their patterns of reactivity are not completely identical in the same patients, and little data have been obtained about ACPAs other than anti-CCP in JIA.…”
Section: Introductionmentioning
confidence: 99%